Underserved Patient Populations With Metastatic Breast Cancer: A Review of Progress and Remaining Challenges - Fatima Cardoso; Rachel Wuerstlein; Tomoyuki Aruga; Renate Haidinger; Matteo Lambertini; Christine Benjamin; Elisenda Llabrés Valentí; Carmen Criscitiello; Matti Aapro; Generosa Grana; Sharon S. Gentry; Eduard Vrdoljak (The Breast Journal)
Breast cancer presents a significant risk to public health and is the primary cause of cancer-related death in women. Awareness of metastatic breast cancer (mBC) continues to increase, and advances have been made; however, challenges remain for many patient populations that do not receive equal opportunities along the treatment pathway. The Underserved Patient Population (UPP) Coalition Task Force, a group of international experts in mBC, held meetings between 2022 and 2023 to prioritise the needs of UPPs and propose solutions. The key unmet needs identified included the following: delayed diagnosis of mBC due to difficulties in the presentation of patients to the healthcare system and a lack of primary care physician and non–breast cancer specialist understanding of the signs and symptoms of mBC; difficulty navigating the mBC patient pathway due to suboptimal use of multidisciplinary care and limited communication between HCPs; unequal access to the most appropriate mBC treatment options and supportive therapy due to the unconscious bias of HCPs, and direct and indirect financial toxicity for patients; and negative impact on QoL resulting from the limited uptake of shared decision-making, low prioritisation of patient preferences and a lack of personalised care. This paper aims to shine light on initiatives supporting underserved patients with mBC, illustrate the remaining gaps in care and call upon the global community to change how care is delivered to UPPs.